A comparative study of the psychological profiles of Indian Railways and Madhya Pradesh National and International Level Male Cricket Players: a pilot study. (17th December 2010) - Bhagirathi, Sameer E; Mehta, Deepak; Chandel, Sudhira
Abstract : The purpose of the study was to find out the comparative result of the Psychological Profiles of Indian Railways and Madhya Pradesh International and National Level Male Cricket Players. The subject's age ranged between 18 and 25 years, they all were selected randomly from the Railways and Madhya Pradesh as U-19 and U-22 Cricket teams. The experts made two groups of 49–49 players, one group made up of Madhya Pradesh cricket players and another group made up of Railways Cricket players, those who are continuously participating at national and international level. The experts used questionnaires of Rainer and Martin's Sports Competition Anxiety Test (SCAT) and the Maudsley Personality Inventory; the questions addressed various aspects of Sports Competition Anxiety and Personality traits of cricket players, respectively. The questionnaire has filled by the Railways and Madhya Pradesh U-19 and U-22 Cricket teams players, respectively. For the evaluation of questionnaire two sample t test was employed, and the findings revealed that there was a significant difference found that is, 2.8 in their Personality parameters, it means Railways Cricketers were better in their Personality as compare to Madhya Pradesh Cricketers and found Insignificant that is, 0.12 in the SCAT, which means there was no difference in Sports Competition Anxiety of Railways Cricketers and Madhya Pradesh Cricketers. Sports Psychology can help a lot in assessing the personality and sports anxiety characteristics of the players or individuals performance in cricket not only demands systematic training to develop physical and physiological variables but also demands training and considerations of psychological characteristics for success in this field.